Customer’s Satisfaction towards the Development of Commercial Organic Fertilizer Packaging - Inthara-udom, Trannaruch; Prommai, Pichet (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
DOI : 10.14456/pnuhuso.2023.9 The main purpose of this research was 1) to study the development of commercial organic fertilizer packaging that influences customer satisfaction and 2) to compare the satisfaction of customers towards organic fertilizer packaging classified by personal factors. 276 customers in Songkhla province were selected by simple random sampling. A set of questionnaires was used to collect data. The data were analyzed by frequency, percentage, mean, standard deviation, t-test, One-way analysis of variance and multiple regression analysis. The findings revealed that: 1) The development of commercial organic fertilizer packaging in terms of packaging design influenced customer satisfaction at 46.3 percent, 2) The development of commercial organic fertilizer packaging in terms of graphic design on the packaging influenced customer satisfaction at 55.5 percent and 3) The customers with different education background and income have different level of satisfaction in commercial organic fertilizer packaging aspect with a statistical significance level of 0.05.